Marina Viličić, PhD in Technical Sciences - Miljanko Lapaine (Kartografija i Geoinformacije, 2019)
On 15 February 2019, Marina Viličić (a graduate engineer of geodesy) defended her doctoral thesis, "Cartographic Analysis of Stjepan Glavač’s Map of 1673". The defence commission consisted of Prof. Dr. Stanislav Frangeš, Dr. Ivka Kljajić, and Prof. Dr. Josip Faričić of the University of Zadar, Department of Geography. The supervisor was Prof. Emeritus Miljenko Lapaine.